Import/Export: Trafficking in Cross-Cultural Shakespearean Spaces - Desmet, Christy (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
This essay examines the phenomenon of cross-cultural Shakespearean “traffic” as an import/export “business” by analyzing the usefulness of the concept crosscultural through a series of theoretical binaries: Global vs. Local Shakespeares, Glocal and Intercultural Shakespeare; and the very definition of space and place within the Shakespearean lexicon. The essay argues that theoretically, the opposition of global and local Shakespeares has a tendency to collapse, and both glocal and intercultural Shakespeares are the object of serious critique. However, the project of cross-cultural Shakespeare is sustained by the dialectic between memorialization and forgetting that attends all attempts to record these cross-cultural experiences. The meaning of crosscultural Shakespeare lies in the interpreter’s agency.